Validation appearance, content and internal consistency of the scale Appraisal of Self-care Agency (ASA) to Costa Rica, for second Spanish version known population healthy - Leiva Díaz, Viriam (2015)
Introduction. This article presents the results of the validation process of appearance, content and internal consistency that was submitted the second version in Spanish of the ASA scale known Costa Rican population healthy. Methodology. This is a transversal, descriptive study of quantitative approach, not experimental and psychometric design, conducted with a sample of 105 people on stage early, middle and late adulthood. Result. The investigation determined that the factorial study (ACP method) with Varimax rotation analysis suggested five factorial axes that explain 60.03% of the total variance in Costa Rica. The outcome of the above domains, highlighted that in most of them the universal requirement category related to prevention of hazards to life, the functioning and human well-being prevails. Conclusion. In Costa Rica, the nurse may have a valid and reliable to measure the ability of self-care agency known in healthy people who are at the stage of adulthood instrument